Comparison of the use of Alvarado and AIR scores as an adjunct to the clinical diagnosis of acute appendicitis in the pediatric population - Aya Musbahi; Darren Rudd; Matei Dordea; Bussa Gopinath; Vijay Kurup (BMJ Publishing Group, 2019)
Background Acute appendicitis is one of the most common causes of acute abdominal pain with an incidence of 1.17 per 1000 and lifetime risk of approximately 7%. It remains the most common indication for emergency abdominal surgery in childhood. Diagnosis of acute appendicitis is particularly difficult in young women and the pediatric population. In the USA, CT imaging is used to avert diagnostic dilemma, however the procedure is associated with radiation risk in this vulnerable population. Additionally, the procedure has high cost and variable availability.Methods A retrospective study involving all suspected pediatric cases of appendicitis between the ages of 5 and 17 who were operated on between 2012 and 2015 was carried out. Data were collated from clinical notes on age, sex, ultrasound findings; postoperative complications, white cell count, neutrophils, C-reactive protein, histology result, and number of days to theater. All patients in the time period were retrospectively scored on the Alvarado and Appendicitis Inflammatory Response (AIR) scores.Results A total of 239 patients between 11 and 17 (mean 13.6±SE) years of age were included in the study. Of these, 79 had preoperative ultrasound, of which 52 were negative, and only one patient had CT scan. 213 of the patients had an appendicectomy and 26 had diagnostic laparoscopy with no appendicectomy. Of the 213 appendixes removed, 71 were histopathologically normal, giving a negative appendectomy rate of 33.3%. 28 appendixes were perforated. The average number of days from admission to theater was 1.0 SE in males and 1.424 in females (p=0.0498). The average number of days from admission to theater in those who had ultrasound was 2.03 days compared with 0.75 in those who did not have ultrasound (p<0.0001). AIR scoring that was high and medium risk showed slightly lower negative appendicectomy rates but not significantly different.Conclusions Our study has found no significant difference between the AIR scores and Alvarado. There is a role for scoring systems to be used to aid in the decision to undergo imaging and as an adjunct to clinical diagnosis.